Perception of ecological aspects as part of flood protection - Dobransky Marian; Bujansky Peter; Zhenjun Gao (MATEC Web of Conferences, 2023)
Modern trends in water management are more than ever inclined towards ecological solutions to avoid technical stream-channel regulation of riverbeds in the design of flood defence measures. Modifications to straighten the riverbeds that were considered in the past, removed the natural meanders of the river, increased the longitudinal slope of the riverbed, and accelerated the outflow from the threatened area. The goals of building protective dams and controlled floodplains are also limited by the negative perception of conservationists and ecologists, which leads to stagnation and discouragement from the proposals. The aim of this article is to compare the given perception of ecological aspects in different countries, how they approach them and how they are applied in studies of flood solutions. Among the ecological aspects, the following points of view will be observed: (1) options for regulation and design of flood areas, (2) duration of flooding time for the ecosystem or the landscape, (3) redefinition of riverfront in cities and (4) concept of resilience.